Pemahaman dan Praktik Pencegahan Tekanan Darah Tinggi di Desa Cilayung (Tinjauan Antropologis) - Anisa Nur Ropika (Universitas Padjadjaran, 2018)
This research discusses the understanding and practice of high blood pressure prevention and treatment in Desa Cilayung using medical anthropology perspective. This research applied qualitative method, in particular, ethnography. The data were collected through participant observation and in-depth interview. The results of this research indicate that people in Desa Cilayung understand high blood pressure as a disease caused by excessive mental pressure, excessive physical activity, and excessive salt consumption. Practices for prevention and treatment include reducing causal factors and taking medicines from biomedical practitioners and ethnomedicine from traditional healers or medicinal plants they obtain from their homegarden. This understanding and practices have been influenced by people’s local belief on disease etiology and its treatment.